Development and Validation of a Predictive Model of Pain Modulation Profile to Guide Chronic Pain Treatment: A Study Protocol - Vincenot, Matthieu; Coulombe-Lévêque, Alexia; Sean, Monica; Camirand Lemyre, Félix; Gendron, Louis; Marchand, Serge; Léonard, Guillaume (Frontiers in Pain Research, 2021)
Introduction Quantitative sensory testing is frequently used in research to assess endogenous pain modulation mechanisms such as Temporal Summation (TS) and Conditioned Pain Modulation (CPM), reflecting excitatory and inhibitory mechanisms, respectively. Numerous studies found that a dysregulation of these mechanisms is associated with chronic pain conditions. In turn, such a patient’s “profile” (increased TS and/or weakened CPM), could recommend different pharmacological treatments. However, the procedure to evaluate these mechanisms is time-consuming and requires expensive equipment that is not available in the clinical setting. In this study, we aim to identify psychological, physiological and socio-demographic markers that could serve as proxies to allow healthcare professionals to identify these pain phenotypes in clinic, and consequently optimize pharmacological treatments. Method We aim to recruit a healthy participant cohort (n=360) and a chronic pain patient cohort (n=108). Independent variables will include psychological questionnaires, pain measurements, physiological measures and sociodemographic characteristics. Dependent variables will include TS and CPM, which will be measured using quantitative sensory testing. We will assess the correlation between TS/CPM and our independent variables, before running a multiple regression analysis on the variables significantly correlated with TS/CPM. The significance thresholds will be set at p=.10 and p=.05, respectively. Perspectives This study will allow us to develop a predictive model to compute the pain modulation profile of individual patients based on their biopsychosocial characteristics. The overarching goal of this study is to provide clinicians with a set of quick and cheap tests, easily applicable in clinical practice to orient pharmacological treatments.